BALIMONT Tri-Strain Probiotic Platform for Skin Radiance Support: Comparative Performance and Human Translational Evidence - Ziraoui, Anas; Beaumont, Charles; Brooks, Tyler (International Journal of Public Health and Medical Research, 2026)
We evaluated a BALIMONT three-strain oral probiotic platform designed for skin radiance support and aligned its 28-day comparative performance dataset with published human evidence on the gut–skin axis. The formulation was organized around Lactobacillus reuteri ATCC 23272, Lactobacillus rhamnosus DSM 20021, and Lactobacillus plantarum DSM 20174, and was developed across lyophilized powder, hard-capsule, and tablet dosage forms. Across the comparative dataset, all multi-strain BALIMONT preparations outperformed the single-strain benchmark. The 2:1:1 lyophilized-powder configuration delivered the strongest observed response, with a 14.2% increase in cheek skin radiance and a 22.6% increase in gut-microbiota Shannon diversity after 28 days. Published human studies provide external support for the translational plausibility of probiotic skin interventions: Lactobacillus plantarum HY7714 improved skin hydration, gloss, and elasticity in a randomized placebo-controlled trial, while an oral probiotic containing Lacticaseibacillus rhamnosus improved acne outcomes in a 12-week randomized trial. Taken together, the BALIMONT platform is best interpreted as a ratio-defined dermonutrition system in which multi-strain complementarity, viable-count control, and dosage-form compatibility jointly support visible skin-quality endpoints. Future confirmatory randomized trials should incorporate dedicated radiance, hydration, sebum, and blemish severity measures.